Nonexistence Proofs for Five Ternary Linear Codes - GURITMAN, S. (MILANG Journal of Mathematics and Its Applications, 2002)
An [n,k, dh-code is a ternary linear code with length n, dimension k and minimum distance d. We prove that codes with parameters [110,6, 72h, [109,6,71h, [237,6,157b, [69,7,43h, and [120,9,75h do not exist.